PROFIL PENGGUNAAN ANTIBIOTIK PASIEN HAEC PASCA OPERASI DI RSUD DR. SOETOMO TAHUN 2015-2018 - Erfano Muhammad Falah (Jurnal Kedokteran Syiah Kuala, 2018)
Abstract. HAEC (Hirschsprung-associated Enterocolitis) is one of serious and life-threatening complication of patient with HD (Hirschsprung’s Disease). The etiology of HAEC is still unknown until now, however, the existence of gram-negative bacterial especially C. Dificille has been linked to occurrence of patient with HAEC. HAEC frequently found at patient with HD post-operative surgery. The treatment for HD patient post-operative with HAEC are rectal irrigation, fluid therapy, and antibiotics. Because of the wide variety of sign and symptoms in HAEC post operative patient, under treatment has always been an issue that can leads to higher mortality in HAEC patient. Data of antibiotics application for HAEC post-operative patient in Dr. Soetomo General Hospital have not been collected. Because of the issue, writer is interested to effectuate case study about the used of antibiotics for HAEC patient post operative in  Dr. Soetomo General Hospital at period 2015-2018.Methods : This is a descriptive observational research that analyze through collecting data from medical record by retrospective. This research is using Total Sampling technique from 38 patients that going through HD operative surgery at Dr. Soetomo General Hospital from 2015 to 2018. From 38 patients that going through operative surgery, five patient experience HAEC as complication post HD operative surgery.Results : Five patient with HAEC with HD post-operative are successfully healed and dismissed from hospital. In four out of five patients Metronidazole was selected as the main antibiotic used (80%). Gentamicin was used in three patients using Metronidazole as the main antibiotic (60%). Ampicillin was used in 2 patients using Metronidazole as the main antibiotic (40%). There was only one patient who used metronidazole as a single antibiotic therapy. Ceftriaxone was used in one patient with Metronidazole as the main antibiotic and was used as a single antibiotic therapy in another patient with sepsis complication and diagnosed with HD at the aged below one week. Keywords : HAEC ; HD ; Hirschsprung-associated Enterocolitis ; Hirschsprung’s Disease ; Antibiotics ; Post-Operative  Abstrak. HAEC (Hirschsprung-associated Enterocolitis) merupakan suatu komplikasi yang serius dan dapat mengancam kehidupan pada pasien HD (Hirschsprung’s Disease). Etiologi dari HAEC masih belum dapat dipastikan sampai sekarang, namun adanya infeksi bakteri C. Dificille berkaitan erat dengan terjadinya HAEC. HAEC adalah salah satu komplikasi yang sering dijumpai pada pasien pasca operasi HD. Penanganan HAEC pasca operasi terdiri dari irigasi rektal, terapi cairan, dan antibiotik. Tanda dan gejala yang diperlihatkan pasien HAEC sangatlah bervariatif sehingga sering menyebabkan penanganan dibawah standar prosedur. Data mengenai penanganan dan terapi antibiotika pada pasien HAEC pasca operasi di RSUD Dr. Soetomo Surabaya belum diketahui, oleh karena itu penulis melakukan penelitian mengenai pemilihan antibiotika pada penanganan pasien HAEC pasca operasi HD di RSUD Dr. Soetomo Surabaya pada tahun 2015-2018.Metode : Penelitian dengan jenis observasional deskriptif yang menggunakan data rekam medis untuk melihat data pasien secara retrospektif. Penelitian menggunakan teknik Total Sampling pada 38 pasien yang menjalani operasi HD di RSUD Dr. Soetomo pada tahun 2015-2018. Pada 38 pasien yang menjalani operasi HD, terdapat 5 pasien mengalami komplikasi HAEC pasca operasi HDHasil : Didapatkan hasil lima pasien dengan HAEC pasca operasi HD sembuh dan keluar rumah sakit (100%). Pada empat dari lima pasien Metronidazol dipilih sebagai penggunaan antibiotik utama (80%). Gentamicin digunakan pada tiga pasien yang menggunakan Metronidazol sebagai antibiotik utama (60%). Ampicillin digunakan pada 2 pasien yang menggunakan Metronidazol sebagai antibiotik utama (40%). Hanya terdapat satu pasien yang menggunakan Metronidazol sebagai terapi antibiotik tunggal. Ceftriaxone digunakan pada salah satu pasien dengan Metronidazol sebagai antibiotik utama dan digunakan juga sebagai terapi antibiotik tunggal pada satu pasien lainnya yang mengalami HD dengan komplikasi sepsis pada usia dibawah satu minggu. Kata kunci : HAEC ;  HD ; Hirschsprung-associated Enterocolitis ; Hirschsprung’s Disease ; Antibiotik ; Pasca Operasi